Human Fibrinopeptides as Antithrombins - Gorman, J. J; Castaldi, P. A (Thrombosis and Haemostasis, 1973)
Human fibrinopeptides have been isolated from purified human fibrinogen and investigations performed on their reactions with thrombin and platelets. Fibrinopeptides A and B had an inhibitory action against the proteolytic action of thrombin but fibrinopeptide A did not impair the esterolytic activity of the enzyme. Studies on thrombin - catalysed platelet aggregation and C14-Serotonin release showed a similar inhibition but the fibrinopeptides had no effect on platelet reactivity with adenosine diphosphate or collagen. These properties of fibrinopeptides were demonstrated in concentrations compatible with a similar effect in localized thrombosis.